Types of diabetes during pregnancy and longitudinal BMI in offspring from birth to age 10 years. Issue 8 (26th February 2021) - Sidell, Margo; Martinez, Mayra P.; Chow, Ting; Xiang, Anny H.
Summary: Objective: To examine longitudinal BMI trajectory from birth to age 10 years in a clinical cohort after exposure to maternal pre‐existing type 1 (T1D), type 2 (T2D), gestational diabetes managed with or without anti‐diabetes medication, and no diabetes during pregnancy. Methods: Data included 218 227 singleton children born in 2008‐2015 from a population‐based integrated healthcare system; 537 exposed to maternal T1D, 7836 to T2D, 6982 to medicated GDM and 12 576 to unmedicated GDM. Differences in BMI over time among groups were assessed by non‐linear mixed‐effects models adjusting for covariates. Results: Children's BMI was significantly lower 6‐months after birth for all diabetes exposed groups compared to no diabetes. Beginning at approximately age 2.5 years, BMI was significantly higher for T1D, T2D and medicated GDM groups compared to the no diabetes group. At age 3, the growth pattern started separating with highest BMI in T1D and T2D groups, followed by medicated GDM, unmedicated GDM, and the no diabetes groups. By age 7, BMI was significantly higher for the unmedicated GDM group compared to the no diabetes group. Adjusted BMI was generally comparable between T1D and T2D groups for all ages. Starting at age 5, T1D, T2D and medicated GDM groups had BMI greater than one SD over the BMI in the no diabetes group. Conclusion: In a clinical cohort with standard diabetes management approaches, a hierarchical BMI growth pattern exists in offspring exposed to different types of diabetes during pregnancy after adjusting for important covariates, starting as early as age 3 years.